Netnography approach for UX research - Hussein, Idyawati; Mahmud, Murni; Md Noor, Nor Laila (ACM, 2016)
This paper discusses on how netnography can be applied to gain an understanding on sensitive research topic in a high power distance culture. The study investigated the frustrations among practitioners in incorporating the User Experience Design (UXD) in software development process. Netnography has been applied to uncover the unspoken behaviors of stakeholders and attitudes of clients who disrespect designers that reflects the UX practitioners frustration on the stakeholiders‘ politics. This findings will be useful in seeking a solution to improve the UXD process. From this work it can be concluded that netnography can be a suitable approach to gain deeper insights into understanding practitioner’s frustrations in UX research study.